Government bond market integration and the EMU: Correlation based evidence - Sebastian Missio (Friedrich-Alexander-Universität Erlangen-Nürnberg, Bavarian Graduate Program in Economics (BGPE), 2012)
In July 1990, the project of the European Monetary Union (EMU) started and finally led to the introduction of the Euro in January 1999. This paper analyses the development of the government bond market integration during the three stages of the EMU. Based on the results from dynamic conditional correlation (DCC) models, the study shows that the integration process was highly advanced but not completed at any point in time and that the degree of integration differentiated between geographical and political regions. It is confirmed statistically that the first, the second and the third stage of the EMU each contributed as a whole to the integration process and that each beginning of a new stage triggered an own wave of government bond market integration progress. Finally, a comparison of government bond market integration with equity market integration is proposed in order to identify the particular reason for the bond market integration in Europe. The results demonstrate that the expectation of real harmonization of fundamental values as opposed to an expectation that countries of the Euro Area will be saved once there is financial distress drives the European government bond market integration.
Keywords: E44; E65; F36; C58; 330; Bond market integration; European Monetary Union; Dynamic conditional correlation; Öffentliche Anleihe; Finanzmarkt; Marktintegration; Europäische Wirtschafts- und Währungsunion; Europäische Wirtschafts- und Währungsunion